Decomposition modes of austenite in 9Cr–W–V–Ta reduced activation ferritic–martensitic steels. (March 2015) - Ravikirana; Mythili, R.; Raju, S.; Saroja, S.; Jayakumar, T.; Rajendra Kumar, E.
<x content-type="archive" xml:space="preserve">Abstract</x> The present paper presents the results of an extensive electron microscopy investigation on the decomposition modes of high temperature austenite in 9Cr–W–V–Ta reduced activation ferritic–martensitic steels. Although the displacive martensitic transformation is predominant on austenitisation, low volume fraction of Fe rich M3C or M23C6 precipitates formed, when the tungsten content exceeded 1 wt-%. The compositional inhomogeneity introduced in the austenite by the nature, chemistry and kinetics of dissolution of the pre-existing carbides is dependent on the steel composition and austenitisation conditions. The extent of repartitioning of tungsten between M23C6 and ferrite largely influences the kinetics of austenite and martensite transformation, for the same austenitisation conditions. Supporting evidence from calorimetry analysis is also presented.